PEMANFAATAN LIMBAH KULIT KOPI DAN SERBUK GERGAJI MENJADI BRIKET SEBAGAI SUMBER ENERGI ALTERNATIF - S.T.,M.T., Hilwatullisan (Politeknik Negeri Sriwijaya, 2015)
Dependence on fuel oil brought Indonesia to the energy crisis seriously. One way to reduce dependence on fossil energy is to develop alternative renewable energy sources. Developing the alternative energy from saw dust waste and coffee skin has a great potential to be used as raw material for the manufacture of briquettes. The purpose of the study was to determine the effects of temperature and composition of briquettes from saw dust waste and coffee skin. Variations in temperature there are 250oC, 300oC, 350oC, 400oC and 450oC for 2 hours with the composition ratio between coffee skin and saw dust waste 75: 25 and 25: 75 as well as the addition of adhesive materials as much as 8%. Dependent variable, there are inherent moisture , ash content, volatile matter, fixed carbon and calorific value. Briquette-shaped cylinder with a height of 2.5 cm and a diameter of 7.5 cm. Based on the research results obtained briquettes in temperature 450oC coffee skin composition and saw dust waste (25:75) with a inherent moisture of 0.87%, 7.84% ash content, volatile matter 23.96%, 67.33% fixed carbon and a calorificvalue of 5800.16 cal /g.